Diffuse Large B-Cell Breast Lymphoma: A Case Series. Issue 10 (11th August 2017) - Al Battah, Afaf H; Al Kuwari, Einas A; Hascsi, Zsolt; Nashwan, Abdulqadir J; Elomari, Halima; Elsabah, Hisham; Al Azawi, Safa; Kohla, Samah; Soliman, Dina; Yassin, Mohamed A
Primary breast lymphoma (PBL) is a rare disease, and few clinicohistopathologic features of the disease have been discussed in previous studies. It represents 2.2% of extranodal lymphomas and constitutes 0.04% to 0.5% of malignant breast neoplasms, despite the clinical and radiographic similarities between breast lymphoma and carcinoma, the prognosis, as reported in the literature, varies. No consensus exists on the best way to treat PBL. However, radiotherapy and chemotherapy were used alone or in combination to treat various cases of PBL. We retrospectively studied 3 cases of PBL of the breast seen in patients attending a tertiary cancer center in Qatar, between 2012 and 2015, in an attempt to determine the common clinical features, therapy, and prognosis of PBL.